2018
DOI: 10.4236/ce.2018.99107
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Approach to Enhance Engineering Education in Argentina: A Case of Study in Signals and Systems

Abstract: We are really interested in improving engineering education by applying an original paradigm. For this reason, the undergraduate course of Signal and Systems was selected as our first field of work, to begin the implementation of this new idea and their promotion within our university community. In this regard, the "active learning approach" (AL) is made up of a series of tools that allow the students to become "actively" involved in the course, getting engaged in the activities proposed to enhance their skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To avoid passive transductions, we suggest that practitioners adopt active learning [19,20] techniques and employ the variation theory of learning [14,21,22] to ensure greater engagement with the semiotic material by the students.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid passive transductions, we suggest that practitioners adopt active learning [19,20] techniques and employ the variation theory of learning [14,21,22] to ensure greater engagement with the semiotic material by the students.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the presence of several initiatives to address these issues at the regional level of South America, for example, in Argentina [3,11] and Uruguay [4][5][6], most of the approaches didn't focus specifically on bridging the gap between the academic domain and problem-solving visions in real-world scenarios. With the intention of resolving the issues which the students have primarily been facing, especially in the undergraduate level of biological engineering in the University, the task of designing a new course was undertaken.…”
Section: Analysis Of the Key Issues In Learning Paradigmsmentioning
confidence: 99%
“…In the digital era, one of the crucial areas which needs to embrace newer technologies and cutting-edge paradigms is education. During the transition from high school to university-level education in Science, Technology, Engineering, and Mathematics (STEM), it has been observed that a significant number of students lack clarity regarding the scope and applications of the career or study program they choose [11], which often reduces their commitment to their chosen career. Especially in the domain of life sciences, the uncertainty among the students especially with respect to the future scope of their career is caused by several factors, including inadequate exposure to the state-of-the-art in the field, or limited access to professional development in parallel to the university courses, or unsatisfactory communication with referents and leaders in the field.…”
Section: Introductionmentioning
confidence: 99%